Assessing the pressure of tennis balls using nonlinear solitary waves: a numerical study - Bagheri, A.; Rizzo, P. (Sports Engineering, 2017)
We present a method based on the propagation of highly nonlinear solitary waves (HNSWs) to measure the internal pressure of tennis balls. HNSWs are compact waves that can form and travel in nonlinear systems such as one-dimensional chains of spherical particles, where they are conventionally generated by the mechanical impact of a striker. The speed, amplitude, and duration of these waves can be tuned by modifying the particles` material or size, or the velocity of the striker. In the present study we numerically investigated the coupling mechanism between the solitary waves propagating along a 1-D granular chain and a tennis ball in contact with the nonlinear medium. A discrete particle model of the beads was coupled to a linear mass-spring-damper model of the tennis ball computed using finite element analysis. Balls with different internal pressures were considered and we found that the time of flight of the HNSWs decreases monotonically with the increase of the internal pressure of the ball.